2022
DOI: 10.3390/ijms23136995
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Wnt Signaling to Vascular Complications in Type 2 Diabetes Mellitus

Abstract: Vascular complications are the leading cause of morbidity and mortality among patients with type 2 diabetes mellitus (T2DM). These vascular abnormalities result in a chronic hyperglycemic state, which influences many signaling molecular pathways that initially lead to increased oxidative stress, increased inflammation, and endothelial dysfunction, leading to both microvascular and macrovascular complications. Endothelial dysfunction represents the initial stage in both types of vascular complications; it repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 106 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Accumulating data suggest an increasing trend in the incidence of type 2 diabetes mellitus, especially in younger people [23,24]. Notably, microvascular complications of diabetes mellitus represent a major threat to public health [25,26]. Simultaneously, DKD is a common microvascular complication of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest an increasing trend in the incidence of type 2 diabetes mellitus, especially in younger people [23,24]. Notably, microvascular complications of diabetes mellitus represent a major threat to public health [25,26]. Simultaneously, DKD is a common microvascular complication of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…hexosamine pathway [48], poly ADP-ribose polymerase (PARP) [49], Advanced glycation end-product (AGE) [50], oxidative stress [51], mitochondrial dysfunction [52], Wnt pathway [53], Hh pathway [54], mitogen-activated protein kinase (MAPK) signaling pathway [55], impaired insulin signaling, Glycogen synthase kinase 3 (GSK3) [56,57], Nuclear factor kappa B (NF-κB) [58], Cyclooxygenase (COX), Lectin-like oxidized low-density lipoprotein (LDL) receptor (LOX) [59], Interleukin (IL) [60], neurotrophic and cellular signaling, tumor necrosis factor (TNF)-α [61], autophagy, satellite glia cells, Schwann cells [62]. Different biochemical mechanisms associated with nerve and neurovascular injury have demonstrated that oxidative stress could modify the typical operation of metabolic mechanisms implicated in DN.…”
Section: Molecular Mechanisms and Pathophysiology Underlying The Path...mentioning
confidence: 99%
“…CVD complications associated with diabetes can be divided into microvascular complications, such as diabetic nephropathy and retinopathy, and AGING macrovascular complications, including diabetic cardiomyopathy, coronary artery disease, etc. [4].…”
Section: Introductionmentioning
confidence: 99%